2020
DOI: 10.3389/fendo.2020.00402
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Performance of Different Lymph Node Staging Systems in Patients With Small Bowel Neuroendocrine Tumors

Abstract: Background: The prognostic significance of the lymph node (LN) classification for small bowel neuroendocrine tumors (SBNETs) remains unknown. The aim of the present study was to evaluate and compare the prognostic assessment of different LN staging systems. Methods: Patients with SBNETs were identified from the Surveillance, Epidemiology, and End Results (SEER) database. The X-tile program was used to determine the cutoff value of the resected lymph nodes (RLNs), negative lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In addition, the prognostic value of the PLN ratio in SBNET patients has also been reported, 26 but if the number of ELNs is small, the PLN ratio is often overestimated and cannot truly reflect the actual state of the patient. As an important indicator of the degree of radical cure, NLNs are an independent prognostic factor in a variety of tumors, including gastric cancer, 16 rectal cancer, 10 colon cancer, 27 and lung cancer 18 but have been seldom reported in SBNETs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the prognostic value of the PLN ratio in SBNET patients has also been reported, 26 but if the number of ELNs is small, the PLN ratio is often overestimated and cannot truly reflect the actual state of the patient. As an important indicator of the degree of radical cure, NLNs are an independent prognostic factor in a variety of tumors, including gastric cancer, 16 rectal cancer, 10 colon cancer, 27 and lung cancer 18 but have been seldom reported in SBNETs.…”
Section: Discussionmentioning
confidence: 99%
“…international cohort study. J Natl Cancer Inst (2012) 104 (10) Conflict of Interest: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest.…”
Section: Figurementioning
confidence: 99%
“…Adding 0.5 to the numerator and denominator avoids division by zero, which aids in stratification of patients without PLNs into different prognostic groups ( 9 ). Recently, LODDS staging was thought a better predictor of survival in the small bowel neuroendocrine tumors compared with LNR and PLN staging ( 10 ). However, the actual prognostic value of LODDS in PanNENs remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although NDLN and NPLN do not contribute to N classification, several studies have confirmed that higher values of NPLN, log odds of positive lymph nodes (LODDS, calculated using the formula: LODDS¼ log NPLN þ0:50 NDLN −NPLN þ0:5 ) or lymph node ratio (LNR, calculated using the formula: LNR¼ NPLN NDLN ) were related to worse prognosis for NSCLC or several other types of malignant tumors [10][11][12][13]. However, of these node classifications, which can obtain the most precise prognosis in lung AC is unclear.…”
Section: Introductionmentioning
confidence: 99%